Preparation of EDTA modified cotton fiber iron complex and catalytic properties for aqueous Cr(VI) reduction and dye degradation - Hongfang Wu (IWA Publishing, 2021)
Cotton fabric was modified with Na2EDTA using a hydrothermal method to introduce surface hydroxyl groups, and subsequent coordination of Fe(III) ions to produce an Na2EDTA modified cotton-fiber-Fe complex (Fe-EDTA-Cotton). After characterization by SEM and FTIR, Fe-EDTA-Cotton was used as a heterogeneous photocatalyst to reduce Cr(VI) and degrade Reactive Red 195 oxidatively, to evaluate its catalytic activity. The results indicated that high Na2EDTA and/or NaH2PO4 concentrations, and/or high hydrothermal temperature increased the carboxyl group content (QCOOH) of the cotton fiber; high Fe content and elevated temperature could enhance coordination. Fe-EDTA-Cotton had a significant photocatalytic function in reducing Cr(VI). Increasing the QFe value of the complex or stronger irradiation favored photocatalytic reduction of Cr(VI) species. Increasing the system's pH did not help the reduction reaction. Fe-EDTA-Cotton could also remove Cr(VI) and Reactive Red 195 simultaneously from aqueous solution, and showed strong photocatalytic capacity. The reduction or oxidation reaction could be regulated by changing Na2S2O8 concentration in the reaction system, which might provide a new way to treat wastewater containing organic pigments and Cr(VI) species. Highlight Hydrothermal process enhanced EDTA modification of cotton fabric.; EDTA-modified cotton fiber Fe complex was prepared.; Cr(VI) removal was improved by its synergistic effect.; Fe complexes can remove Cr (VI) and organic dyes from aqueous solution in one bath.; The work might provide a new way to purify the wastewater containing organic pigments and Cr (VI) species.;